RECASTING THE DISCIPLINES UNDER THE FRAMEWORK OF ISLAM: Lessons from the Textbook Writing Initiative at Universitas Islam Indonesia - Maharika, Ilya Fadjar; Wahid, Fathul; Nur Kholis (Direktorat Pondok Pesantren Universitas Islam Indonesia, 2021)
The idea of integrating human knowledge and Islamic values, or Islamization of knowledge, has triggered fruitful discussions, but the concrete output in terms of an ‘Islamized' textbook has not occurred. In this paper, we report practical insights from the textbook writing initiative at Universitas Islam Indonesia (UII) to materialize the idea. Our reflection on the ongoing process has identified several challenges. These include diversity of the disciplines, limited exposure to the philosophy of knowledge, lack of ready-to-use integration methods and inadequate mastery of the Islamic legacy. To cope with the challenges, we have taken several actions, including arranging a series of workshops (on the philosophy of knowledge and integration strategies), providing relevant literature and offering technical assistance. In concluding, we present an overview of the future directions that UII will take. Keywords: textbook writing; Islamization of knowledge; integration of human knowledge.